1996
DOI: 10.1021/jp960059l
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding Effect on 13C and Proton Hyperfine Couplings of [4-13C]-Labeled Ubisemiquinones in Vitro

Abstract: EPR spectra of ubiquinone-0 (UQ 0 ) and UQ 10 anion radicals selectively labeled with 13 C at the 4-CdO position are reported. The environmental effect on the 4-13 C splitting constant was studied in mixed solvents in which the molar fraction of the protic component was changed over a wide range. The quinones were electrochemically reduced, with cyclic voltammetry and concomitant optical spectroscopy being performed as controls. The value and the sign of the 4-13 C hyperfine splitting constant strongly depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
(188 reference statements)
4
16
0
Order By: Relevance
“…The isotropic 13 Chfcs, including signs obtained from the EPR spectra, are shown in Table 2. They agree well with the values published for (4-13 C) ubisemiquinone-10 [29]. ENDOR experiments were performed in liquid solutions yielding accurate values for the proton hfcs given in Table 2.…”
Section: Isotropic Liquid Solutionssupporting
confidence: 86%
See 3 more Smart Citations
“…The isotropic 13 Chfcs, including signs obtained from the EPR spectra, are shown in Table 2. They agree well with the values published for (4-13 C) ubisemiquinone-10 [29]. ENDOR experiments were performed in liquid solutions yielding accurate values for the proton hfcs given in Table 2.…”
Section: Isotropic Liquid Solutionssupporting
confidence: 86%
“…6 1/3Tr(A) is the isotropic part obtained from the full tensor. a l , o is the isotropic hfc measured in liquid solution with generally good agreement concerning magnitudes and signs of as" measured independently in [9,10,29] for UQo' and UQ I O' in alcohols and DME. of the molecules could not be detected in the accessible temperature range (150-330 K) limited by solvent properties.…”
Section: Isotropic Liquid Solutionssupporting
confidence: 67%
See 2 more Smart Citations
“…231 This principal is verified by the ab initio studies of neutral and anionic 1,4-benzoquinone-water clusters by Manojkumar et al 232 They observed that when two water molecules are complexing with 1,4-benzoquinone, a conformer exhibiting a H-bond between two water molecules (W 2 Q) is energetically more favoured than the conformer WQW in which there is no direct interaction between the water molecules. The geometry of the structures were optimized at MP2 and B3LYP level using the 6-311++G** basis set.…”
Section: Computational Investigations On 14-benzoquinonesmentioning
confidence: 83%